Discovery of Hyptis pseudolantana in Jalisco and Michoacán, and description of H. cualensis and H. macvaughii (Ocimeae, Lamiaceae), two new species from western Mexico - González-Gallegos, Jesús Guadalupe; Castro-Castro, Arturo; Flores-Argüelles, Alejandra; Romero-Guzmán, Ariosto Rafael (Phytotaxa, 2014)
The distribution of Hyptis pseudolantana is documented in the states of Jalisco and Michoacán, species previously reported exclusively from the state of Guerrero, Mexico. An expanded description, distribution map and photographs are provided for it. Hyptis cualensis and H. macvaughii are also described and illustrated by photographs, as two new species from the Mexican states of Jalisco and Nayarit, respectively. Also, an identification key to species of tribe Hyptidinae in western Mexico is provided.